2014
DOI: 10.1186/1752-1947-8-153
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral extradural hematoma following decompressive craniectomy for acute subdural hematoma (the value of intracranial pressure monitoring): a case report

Abstract: IntroductionDecompressive surgery for acute subdural hematoma leading to contralateral extradural hematoma is an uncommon event with only few cases previously reported in the English medical literature.Case presentationThe present study describes the case of a 39-year-old White Brazilian man who had a motorcycle accident; he underwent decompressive craniectomy for the treatment of acute subdural hematoma and evolved contralateral extradural hematoma following surgery.ConclusionThe present case highlights the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…Few cases of contralateral EDH following decompressive surgery for TBI have been reported. 5 EDH is commonly seen in neurosurgical practice, but in this report, we present two extremely rare cases and causes of postoperative EDH.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Few cases of contralateral EDH following decompressive surgery for TBI have been reported. 5 EDH is commonly seen in neurosurgical practice, but in this report, we present two extremely rare cases and causes of postoperative EDH.…”
Section: Introductionmentioning
confidence: 83%
“…[25][26][27][28][29][30] Panourias et al, Matsuno et al, and Meguins et al reported contralateral epidural hematoma after decompressive craniectomy for acute subdural hematoma. 5,31,32 Shen et al evaluated published data via Pubmed and found a rate of 2.4% for contralateral EDH after acute subdural hematoma. The average patient age was 35, males were in the majority and the main cause of injury was traffic accident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A maioria dos trabalhos coletados foram relatos de casos 3,6,10,23,24,26,29,35 e estudos observacionais com análise retrospectiva 17,22,38,42,43,47 . As observações radiológicas com maior significância foram relatadas por Talbott et al 43 .…”
Section: Características Gerais Dos Estudosunclassified
“…Uma das complicações com desfecho mais desfavorável, secundário a CD, é o desenvolvimento de HE contralateral durante ou nas horas seguintes a cirurgia 17,22,23,24,26,33 . A formação de HE no trauma é comum 20 , entretanto, quando secundário a CD, observamos uma taxa de incidência significantemente menor 43 .…”
Section: B) Anormalidade Pupilarunclassified